Penguatan Pemahaman Konsep Siswa Kelas V pada Materi Bencana Alam melalui Model RADEC - Nurma Yunita; Atep Sujana; Ani Nur Aeni (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to determine the effect of the RADEC learning model on the conceptual understanding of fifth-grade students in the subject of natural disasters. The method used is a quasi-experiment with a nonequivalent control group design involving an experimental class and a control class. The research instruments consisted of pretest and posttest to measure students' conceptual understanding. The results of the study showed that there was an improvement in conceptual understanding in both classes, both those using the RADEC model and the direct instruction learning model. In the experimental class, the average score increased from 61.20 to 73.99, while in the control class it increased from 60.00 to 68.55. Statistical test results showed that there were significant differences before and after learning in each class. However, there was no significant difference between the two classes after learning. Nevertheless, the N-Gain results indicate that the improvement in the experimental class was higher compared to the control class. Thus, it can be concluded that the RADEC learning model has a better potential in enhancing students' conceptual understanding, although it does not show a statistically significant difference compared to the direct learning model.